Comparison of nexus low risk criteria and Canadian cervical spine rule in blunt neck trauma - Dahal, Ram Krishna; Paudel, Sushil; Kafle, Dinesh (Grande Medical Journal, 2024)
BackgroundThe Canadian C-Spine (cervical-spine) Rule (CCR) and the National Emergency X-Radiography Utilization Study (NEXUS) Low-Risk Criteria (NLC) are guidelines for the use of cervical-spine radiography in patients with blunt neck trauma and polytrauma. It is unclear how the two decision rules compare in terms of clinical performance in our setting. MethodWe conducted a prospective observational study in 150 patients in emergency department of IOM TUTH comparing the CCR and NLC as applied to patients with blunt neck trauma and polytrauma. The sensitivity, specificity, and reduction in radiographs were analysed and compared.ResultAmong the 150 patients, the CCR was more sensitive than the NLC (100 % vs. 83.33%) and more specific (47.9 % vs. 42.3%) for injury, and its use would have resulted in lower radiography rates by (46 % vs. 42.33%). Using CCR no potential clinically important cervical spine injuries was missed but using NLC one clinically important cervical spine injury was missed.ConclusionFor blunt neck trauma and polytrauma patients who are in stable condition, the CCR is superior to the NLC with respect to sensitivity and specificity for cervical-spine injury, and its use would result in reduced rates of radiography. Further studies in larger sample size need to follow rigorous methodologic procedures to ensure that the findings are as free of bias as possible.